Between Elites and Society: The Politics of Territorial Splits in a Decentralizing Era, Case of Lebak District, Indonesia - Mahpudin Mahpudin; Ika Arinia Indriyany; M Dian Hikmawan (Universitas Sultan Ageng Tirtayasa, 2021)
This article studies the political struggles of local society in South Lebak who want to split from Lebak District. The reasons are ineffective and inefficient public services, abundant natural resource potential, and political dynasty saturation. Therefore, they continue to negotiate their territorial areas. This article attempts to answer how territorial politics works in the process of territorial splits. The results reveal: first, the political elite used the issue of territorial splits for electoral matters. Second, territorial splits are motivated not only by a group of elites in South Lebak or local politicians, but also by the local people's desire for long-term prosperity and exceptionally effective and efficient public services. However, the interests of the local elite groups are more dominant. This study found that there is a link between the interests of society and the local elites.Keywords: decentralization; election; elites; politics of territorial splits; South Lebak.